21st Century Cognitive Behavioural Therapy for Anger: A Systematic Review of Research Design, Methodology and Outcome. Issue 4 (21st February 2018) - Fernandez, Ephrem; Malvaso, Catia; Day, Andrew; Guharajan, Deepan
Abstract : Background: Past reviews of cognitive behavioural therapy (CBT) for anger have focused on outcome in specific subpopulations, with few questions posed about research design and methodology. Since the turn of the century, there has been a surge of methodologically varied studies awaiting systematic review.Aims: The basic aim was to review this recent literature in terms of trends and patterns in research design, operationalization of anger, and covariates such as social desirability bias (SDB). Also of interest was clinical outcome.Method: After successive culling, 42 relevant studies were retained. These were subjected to a rapid evidence assessment (REA) with special attention to design (ranked on the Scientific Methods Scale) measurement methodology (self-monitored behaviour, anger questionnaires, and others' ratings), SDB assessment, and statistical versus clinical significance.Results: The randomized controlled trial characterized 60% of the studies, and the State Trait Anger Expression Inventory was the dominant measure of anger. All but one of the studies reported statistically significant outcome, and all but one of the 21 studies evaluating clinical significance laid claim to it. The one study with neither statistical nor clinical significance was the only one that had assessed and corrected for SDB.Conclusions: Measures remain relatively narrow in scope, but study designs have improved, and the outcomes suggest efficacy and clinical effectiveness. In conjunction with previous findings of an inverse relationship between anger and SDB, the results raise the possibility that the favourable picture of CBT for anger may need closer scrutiny with SDB and other methodological details in mind.